OPTIMIZATION OF DOUBLY REINFORCED BEAM DESIGN USING SIMULATED ANNEALING - SIMON OLAYIWOLA ADEREMI OLAWALE; OLUTOSIN PETER AKINTUNDE; MOSES OLADIPUPO AFOLABI; OLUWOLE AKINYELE AGBEDE (Journal of Engineering Studies and Research)
The optimization of the doubly reinforced concrete beam was investigated in this paper using the simulated annealing. Materials costs are considered as the objective function. The variables are the width, depth, compression steel, tension steel and cost. The constraints are the ultimate moment of resistance, compression/tension-steel ratio, minimum and maximum area of reinforcements. At the concrete compressive strength of 25 MPa, it is demonstrated that simulated annealing method can be used to optimize the design of concrete beams.